Transcatheter aortic valve replacement in quadricuspid aortic valve: a systematic review and meta-analysis - Khalifa, Mostafa A.; Hashim, Hashim Talib; Shimal, Aya Ahmed; Riyas Mohamed, Fathima Raahima; Ragunathan, Srinithi; Al Sakini, Ahmed Sermed; Elbadawi, Mohamed H.; Irfan, Mohammed Rushdhi; Moqbel, Ibrahim; Almualed, Marwah Mohammed; Al-Ghuraibawi, Mohammedbaqer; Al-Aboudi, Batool S. (Frontiers in Cardiovascular Medicine, 2025)
BackgroundWhile Transcatheter Aortic Valve Replacement (TAVR) is now a standard treatment for severe aortic stenosis, its use in patients with quadricuspid aortic valves (QAV) presents unique challenges. This review analyzes current evidence to guide clinicians in managing aortic stenosis in this complex valve morphology.MethodFollowing PRISMA guidelines, a comprehensive literature search was conducted across multiple databases up to August 15, 2024. A random-effects model was used for meta-analysis, focusing on 30-day mortality and procedural success, with secondary outcomes including paravalvular leak incidence, pacemaker insertion, hemodynamic changes, and NYHA functional class improvement.ResultsA total of 11 case reports/series were analyzed, involving 17 adult patients with QAV. Participants had a mean age of 73.80 ± 5.07 years. The mean left ventricular ejection fraction was 41.6%, and the mean annulus area was 595.5 mm2. Most patients (64.7%) underwent transfemoral procedures, with nearly 70% receiving a J-valve or Edwards SAPIEN 3 device. All procedures were largely successful, though 29.4% experienced leakage or regurgitation. Aortic pre-dilation was done in 41.2% of cases. The mean procedural duration was 102 min, with a fluoroscopic duration of 15 min. No patients experienced aortic post-dilation, and one (5.8%) had an atrioventricular block within 30 days post-procedure.ConclusionTAVR is an effective and growing treatment for high-risk patients with aortic valve disease, including those with QAV. While it has high success rates and challenges (i.e., post-operatively). Future studies should focus on long-term valve durability.